Development of a Web-Based Academic Information System for Politeknik Anika Palembang Using the Web Engineering Method - Triana Wulandari (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2024)
The rapid development of information technology in higher education has transformed academic data management systems. At Politeknik Anika Palembang, academic operations such as student registration, course scheduling, and grade entry were previously managed through a desktop-based system requiring manual administrative input. This approach limited accessibility and data efficiency.This study focuses on the development of a web-based Academic Information System (SIAKAD) utilizing the Web Engineering (WE) method. The WE framework emphasizes systematic and structured web application development. The system was implemented using PHP and MySQL for the back end, while HTML and CSS were applied for the front end.System testing employed the Black Box Testing approach to evaluate functionality and reliability. The results confirmed that all components met functional requirements, allowing administrators, lecturers, and students to access academic data efficiently.